Language Features Used by Jerry Lorenzo in the Mavericks with Mav Carter Podcast - Charmelyn Michelia; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
This study aims to find out the language features used by Jerry Lorenzo in the Mavericks with Mav Carter Podcast. For this study, the writers used Lakoff’s (2004) and Coates’ (2013) language features theory. This study was done using a qualitative approach in which the writers transcribed and analyzed all of Jerry’s utterances which contain language features. The writers discovered that Jerry used the following language features: adjectives, hedges, tag questions, intensifiers, grammar, politeness, commands and directives, minimal responses, and compliments. Based on the findings of Jerry’s language features, it can be concluded that men can use women’s language features too. The language features found were influenced by the context and topic of the conversation.